A Multimodal Analgesic Protocol Reduces Opioid-Related Adverse Events and Improves Patient Outcomes in Laparoscopic Sleeve Gastrectomy - Ng J.J. (Springer New York LLC, 2018)
10.1007/s11695-017-2790-7